2017
DOI: 10.1371/journal.pone.0174718
|View full text |Cite
|
Sign up to set email alerts
|

T cell subtypes and reciprocal inflammatory mediator expression differentiate P. falciparum memory recall responses in asymptomatic and symptomatic malaria patients in southeastern Haiti

Abstract: Asymptomatic Plasmodium falciparum infection is responsible for maintaining malarial disease within human populations in low transmission countries such as Haiti. Investigating differential host immune responses to the parasite as a potential underlying mechanism could help provide insight into this highly complex phenomenon and possibly identify asymptomatic individuals. We performed a cross-sectional analysis of individuals who were diagnosed with malaria in Sud-Est, Haiti by comparing the cellular and humor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 104 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…IL-8 is a chemoattractant cytokine known to be involved in neutrophil recruitment and activation, and previously associated with severe malaria pathogenesis (73,78). A recent study reported higher levels of IL-8 production by PBMCs from asymptomatic individuals compared to symptomatic carriers (86). Furthermore, the Malian Fulani ethnic group who are known to be less susceptible to Plasmodium falciparum malaria as reflected by lower parasitemia and fewer clinical symptoms exhibited a higher level of IL-8 than sympatric ethnic groups (87).…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 is a chemoattractant cytokine known to be involved in neutrophil recruitment and activation, and previously associated with severe malaria pathogenesis (73,78). A recent study reported higher levels of IL-8 production by PBMCs from asymptomatic individuals compared to symptomatic carriers (86). Furthermore, the Malian Fulani ethnic group who are known to be less susceptible to Plasmodium falciparum malaria as reflected by lower parasitemia and fewer clinical symptoms exhibited a higher level of IL-8 than sympatric ethnic groups (87).…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 and IL-12 work together to activate interferon γ (IFN-γ), which is necessary for the activation of monocyte proinflammatory function in order to facilitate parasite clearance [ 48 ]. Upon in vitro exposure to P. falciparum , production of GM-CSF, MIP-1β, or IL-34 cytokines initiates the immunity mechanism with lower parasite loads (premunition) by opsonic phagocytosis and cytokine secretions by monocytes [ 49 ]. Exposure of these cytokines, specifically TNF-α and IFN-γ, regulates iRBC uptake and endothelial cell activation by increasing the expression of ICAM-1 and other adhesion molecules by endothelial cells [ 50 ].…”
Section: Cytokine Productionmentioning
confidence: 99%
“…Research on host recognition has found that P. falciparum GPI is also recognized by CD1d-restricted NKT cells [101]. In contrast to in vitro results and co-culture experiments, human CHMI studies have failed to indicate that NKT recognition of P. falciparum antigens is as prevalent during early stages of infection [102][103][104]. However, during CHMI lymphopenia is commonly observed after parasites are released from the liver, which includes a reduction in NKT cells.…”
Section: Monocytesmentioning
confidence: 99%